Розробка та експериментальна оцінка ефективності застосування контролера диференційованого внесення добрив в системі точного зелеробства - Заєць, Максим Леонідович; Погребніченко, Павло Костянтинович; Zayets, Maksym; Pohrebnichenko, Pavlo (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті запропоновано низьковартісний модернізований контролер диференційованого внесення (VRAC), який враховує неоднорідність ґрунту та сприяє впровадженню технологій змінної норми. У межах виробничих полів спостерігається значна просторова варіабельність ґрунтових умов, що впливає на ефективність використання ресурсів і продуктивність культур. Система базується на платформі Raspberry Pi з використанням RTK-сумісної GNSS, крокового двигуна та енкодера колеса. Контролер забезпечує високоточне регулювання норми внесення в реальному часі відповідно до карт-завдань. Реалізація за принципом plug-and-play дозволяє використовувати систему для диференційованого висіву та внесення добрив. Експериментально підтверджено високу точність роботи (97,17 %), низьку похибку (RMSE 4,57; R2 = 0,994) та швидку реакцію системи. Запропоноване рішення є доступним і сприяє розвитку точного землеробства. /// EN: Spatial heterogeneity of agro-physical and agro-chemical soil properties is one of the key challenges of modern agriculture, as it leads to uneven plant development, inefficient use of fertilizers and other resources, and may reduce production economic efficiency. In modern agrotechnology development, particular importance is given to the implementation of intelligent process control systems that allow adapting material application rates to the actual conditions of each field zone. The development of low-cost and technically accessible devices for implementing precision agriculture principles is an important task, since the high cost of commercial systems often limits their use among small and medium-sized producers. The proposed Variable Rate Applicator Controller (VRAC) is aimed at reducing the financial cost of technology implementation by using an open hardware architecture and affordable electronic components. The system is based on the Raspberry Pi platform and uses an RTK-compatible Global Navigation Satellite System to ensure high-precision positioning of the machine in field conditions. Additionally, a wheel encoder is used to measure travelled distance and calculate instantaneous movement speed while minimizing slip error, enabling accurate determination of motor rotation speed (RPM). The Raspberry Pi platform processes input data and implements dynamic control algorithms for material application rates according to predefined prescription maps. Experimental results showed that the average switching time between application rates (from 267 to 45; from 45 to 241; from 241 to 128; from 128 to 218; from 218 to 160 kg/ha) is 0.864 s at operating speeds of 8, 11, 16, 19, 24, and 32 km/h. The average coefficient of variation of system performance is 4.59, the control accuracy is 97.17 %, and the root mean square error (RMSE) is 4.57. The coefficient of determination R2 is 0.994, indicating a high agreement between the set and actual parameter values. The average standard deviation of seeding rate is 1.76 kg. The modular plug-and-play architecture allows the controller to be integrated into existing agricultural machinery without significant structural modification. This provides opportunities for gradual technical modernization of farms and promotes the wider adoption of digital technologies in agricultural production. Therefore, the affordability of the proposed solution, high system accuracy, and the possibility of upgrading existing machinery make the developed controller a promising tool for improving technological process efficiency and ensuring environmentally safe and sustainable agricultural development.
Evaluation of the effectiveness of a sprayer with a dosage rate controller at variable operating speed
Keywords: точне землеробство; диференційоване внесення; контролер VRAC; Raspberry Pi; GNSS- навігація; кроковий електродвигун; автоматизоване керування; змінна норма внесення; агротехнологічні системи; precision agriculture; variable rate application; VRAC controller; GNSS positioning; stepper motor; automated control; variable rate seeding; agrotechnological systems